ChemInform Abstract: Well‐Dispersed and Size‐Controlled Supported Metal Oxide Nanoparticles Derived from MOF Composites and Further Application in Catalysis. Issue 37 (September 2015) - Liu, Hong; Zhang, Suoying; Liu, Yayuan; Yang, Zhuhong; Feng, Xin; Lu, Xiaohua; Huo, Fengwei
Abstract Review: 50 refs.